(untitled) (Swiss Medical Weekly, 2021)
AIMS The Centor criteria and the FeverPAIN score are recommended for guiding antibiotic prescription for tonsillitis, but they are not validated for this purpose. We aimed to identify risk factors for peritonsillar abscess in group A haemolytic streptococcus-negative tonsillitis and to test the performance of clinical scores and laboratory tests. METHODS In a retrospective case-control study at two regional hospitals from January 2015 to June 2018, we identified all cases of peritonsillar abscess and used propensity score matching utilising age and gender to select two controls per case from all patients who had a rapid group A haemolytic streptococcus antigen test in the emergency department. Exclusion criteria were age <18 years, documented refusal and a positive antigen test. We abstracted patient history, physical examination and results of laboratory testing. Logistic regression analysis was used to identify risk factors. RESULTS We included 141 cases of peritonsillar abscess, matched with 282 controls. Higher Centor score, C-reactive protein and white blood cell count were significantly associated with peritonsillar abscess, but had a low performance for predicting the latter (area under the receiver operator characteristic curve [ROC AUC] 0.76). The FeverPAIN score was not associated with peritonsillar abscess (ROC AUC 0.51). In the multivariable analysis, difficulty swallowing (odds ratio [OR] 18.4, 95% confidence interval [CI] 6.58–51.2), dyspnoea (OR 10.2, 95% CI 1.18–89.0), tonsillar swelling (OR 4.21, 95% CI 1.39–12.7) and unilateral signs and symptoms (OR 146, 95% CI 40.9–522) were risk factors of peritonsillar abscess. CONCLUSION The Centor criteria, as well as C-reactive protein and white blood cell count, have a low discriminatory performance, and the FeverPAIN score is not useful in identifying patients at risk for peritonsillar abscess in group A haemolytic streptococcus-negative tonsillitis. To guide a rational antibiotic prescription, new decision tools need to be developed. These might include items such as difficulty swallowing, dyspnoea, tonsillar swelling and unilaterality.